La metodología del docente en el aprendizaje de los estudiantes migrantes en la Básica Media de la Escuela de Educación Básica "Jesús Infante" cantón Riobamba, año lectivo 2022- 2023 - Núñez Cando, Iván Javier (2023)
In educational centers there are students from different cities, countries, geographical areas, these students mostly have different customs, ways of acting and behaving, resulting in classrooms being a multicultural space, with the teacher being the main entity of power, include all their students in the same spaces, this work can be a little complicated, therefore the main objective of this research is to identify the methodologies that the teacher uses for the learning of migrant students at the "Jesús Infante" School of Basic Education, period 2022_2023, where extremely important information could be obtained thanks to the data collection technique, an interview was used for the teachers whose questions were intended to know the methods that teachers use with migrant children, on the other hand, the survey instrument under the questionnaire tool, which was applied to migrant students. It can be announced that the objectives set out in the research were achieved. Taking the first variable as a reference, it was possible to identify the different methodologies that teachers currently use to work with migrant students, in which collaborative and cooperative work, and the DUA methodology can be highlighted, in the same way, referring to the second variable, it can be revealed that teachers achieve adequate learning in migrant children for their educational and social development, since the content given in school is intended to be useful for life.